A novel, two-step top seeded infiltration and growth process for the fabrication of single grain, bulk (RE)BCO superconductors. (27th July 2016) - Namburi, Devendra K; Shi, Yunhua; Palmer, Kysen G; Dennis, Anthony R; Durrell, John H; Cardwell, David A
Abstract: A fundamental requirement of the fabrication of high performing, (RE)–Ba–Cu–O bulk superconductors is achieving a single grain microstructure that exhibits good flux pinning properties. The top seeded melt growth (TSMG) process is a well-established technique for the fabrication of single grain (RE)BCO bulk samples and is now applied routinely by a number of research groups around the world. The introduction of a buffer layer to the TSMG process has been demonstrated recently to improve significantly the general reliability of the process. However, a number of growth-related defects, such as porosity and the formation of micro-cracks, remain inherent to the TSMG process, and are proving difficult to eliminate by varying the melt process parameters. The seeded infiltration and growth (SIG) process has been shown to yield single grain samples that exhibit significantly improved microstructures compared to the TSMG technique. Unfortunately, however, SIG leads to other processing challenges, such as the reliability of fabrication, optimisation of RE2 BaCuO5 (RE-211) inclusions (size and content) in the sample microstructure, practical oxygenation of as processed samples and, hence, optimisation of the superconducting properties of the bulk single grain. In the present paper, we report the development of a near-net shaping technique based on a novel two-step, buffer-aided top seeded infiltration and growth (BA-TSIG) process, which has been demonstrated to improve greatly the reliability of the single grain growth process and has been used to fabricate successfully bulk, single grain (RE)BCO superconductors with improved microstructures and superconducting properties. A trapped field of ∼0.84 T and a zero field current density of 60 kA cm −2 have been measured at 77 K in a bulk, YBCO single grain sample of diameter 25 mm processed by this two-step BA-TSIG technique. To the best of our knowledge, this value of trapped field is the highest value ever reported for a sample fabricated by an infiltration and growth process. In this study we report the successful fabrication of 14 YBCO samples, with diameters of up to 32 mm, by this novel technique with a success rate of greater than 92%.